Validation of the Impostor Phenomenon among Managers - Rohrmann, Sonja; Bechtoldt, Myriam N.; Leonhardt, Mona (Frontiers in Psychology, 2016)
Following up on earlier investigations, the present research aims to validate the construct impostor phenomenon by taking personality correlates into account and to examine whether the impostor phenomenon is a construct in its own right. In addition, gender effects as well as effects on working style and stress or strain are examined. In an online study we surveyed a sample of N = 242 individuals occupying leadership positions in different sectors. Confirmatory factor analyses provide empirical evidence for the discriminant validity of the impostor phenomenon. In accord with earlier studies we show that the impostor phenomenon is accompanied by higher levels of anxiety, dysphoric moods, emotional instability and a generally negative self-evaluation. The study does not reveal any gender differences concerning the impostor phenomenon. With respect to working styles, persons with an impostor self-concept tend to show perfectionist as well as procrastinating behaviors. Moreover, they report being more stressed and strained by their work. In sum, the findings show that the impostor phenomenon constitutes a dysfunctional personality style. Practical implications are discussed.